Pengaruh Struktur Kepemilikan Terhadap Kinerja Perusahaan Pada Sektor Keuangan Yang Tercatat Di Bursa Efek Indonesia Pada Tahun 2007-2010 - Rini Tri Hastuti; Rousilita Suhendah (Jurnal Ekonomi, 2015)
This research examines the effect of insider ownership and institutional ownership on corporate performance in the financial sector that was listed on the Indonesia Stock Exchange in 2007-2010. There is 11th banking on this sample with multiple purposive sampling criteria. Research data was collected from the Indonesian Capital Market Directory. These research findings are insider ownership significant affected operational expenses to operating income ratio and loan to deposit ratio. But this failed to examine whether institutional ownership affects operational expenses to operating income ratio and loan to deposit ratio. The result of this study revealed that insider ownership and institutional ownership did not affect leverage.